Optimization of steady‐state free precession MRI for lung ventilation imaging with 19F C3F8 at 1.5T and 3T. Issue 2 (2nd November 2018) - Maunder, Adam; Rao, Madhwesha; Robb, Fraser; Wild, Jim M.
Abstract : Purpose: To optimize 19 F imaging pulse sequences for perfluoropropane (C3 F8 ) gas human lung ventilation MRI considering intrinsic in vivo relaxation parameters at both 1.5T and 3T. Methods: Optimization of the imaging parameters for both 3D spoiled gradient (SPGR) and steady‐state free precession (SSFP) 19 F imaging sequences with inhaled 79% C3 F8% and 21% oxygen was performed. Phantom measurements were used to validate simulations of SNR. In vivo parameter mapping and sequence optimization and comparison was performed by imaging the lungs of a healthy adult volunteer. T1 and T2 * mapping was performed in vivo to optimize sequence parameters for in vivo lung MRI. The performance of SSFP and SPGR was then evaluated in vivo at 1.5T and 3T. Results: The in vivo T2 * of C3 F8 was shown to be dependent upon lung inflation level (2.04 ms ± 36% for residual volume and 3.14 ms ± 28% for total lung capacity measured at 3T), with lower T2 * observed near the susceptibility interfaces of the diaphragm and around pulmonary blood vessels. Simulation and phantom measurements indicate that a factor of 2‐3 higher SNR can be achieved with SSFP when compared with optimized SPGR. In vivo lung imaging showed a 1.7 factor of improvement in SNR achieved at 1.5T, while the theoretical improvement at 3T was not attained due to experimental SAR constraints, shorter in vivo T1, and B0 inhomogeneity. Conclusion: SSFP imaging provides increased SNR in lung ventilation imaging of C3 F8 demonstrated at 1.5T with optimized SSFP similar to the SNR that can be obtained at 3T with optimized SPGR.